Thermally Stable MAPbI3 Perovskite Solar Cells with Efficiency of 19.19% and Area over 1 cm2 achieved by Additive Engineering. Issue 28 (19th May 2017) - Wu, Yongzhen; Xie, Fengxian; Chen, Han; Yang, Xudong; Su, Huimin; Cai, Molang; Zhou, Zhongmin; Noda, Takeshi; Han, Liyuan
Abstract : Solution‐processed perovskite (PSC) solar cells have achieved extremely high power conversion efficiencies (PCEs) over 20%, but practical application of this photovoltaic technology requires further advancements on both long‐term stability and large‐area device demonstration. Here, an additive‐engineering strategy is developed to realize a facile and convenient fabrication method of large‐area uniform perovskite films composed of large crystal size and low density of defects. The high crystalline quality of the perovskite is found to simultaneously enhance the PCE and the durability of PSCs. By using the simple and widely used methylammonium lead iodide (MAPbI3 ), a certified PCE of 19.19% is achieved for devices with an aperture area of 1.025 cm 2, and the high‐performing devices can sustain over 80% of the initial PCE after 500 h of thermal aging at 85 °C, which are among the best results of MAPbI3 ‐based PSCs so far. Abstract : By enhancing the crystalline quality of the simple and widely used MAPbI3 perovskite through additive engineering, unprecedented photovoltaic performance and thermal stability are achieved. A certified efficiency of 19.19% is obtained for devices with active area over 1 cm 2, and the high‐performing devices show unprecedented durability, maintaining >80% of the initial efficiency after 500 h of thermal aging at 85 °C.